The method for improving stability of construction project schedules through buffer allocation - Jaśkowski, Piotr; Biruk, Sławomir (Technological and Economic Development of Economy, 2011)
The actual completion time of construction projects is rarely in accordance with initial plans. This is due to unforeseen events that affect the project execution. In the paper, the authors propose a method of improving the construction schedule reliability. The method is based on the idea of buffers allocation, whose proper sizing helps to reduce negative effects of random conditions on the progress and efficiency of project activities. The authors adopt a proactive approach to the construction of robust schedules to cope with multiple disruptions during project execution, applicable to two processes starting policies (as soon as possible or no sooner than on a predefined date). The proposed method, based on simulation technique and mathematical programming, was illustrated by an example. The results obtained by means of the proposed method were compared, in terms of schedule stability, to those of the float factor heuristic and starting time criticality heuristicprocedures. The method allowed reducing cost of deviations from the planned activity start dates in random conditions.Article in English.Statybos vykdymo grafiko stabilumo užtikrinimas paskirstant laiko rezervusSantrauka. Tikrasis statybos projektų baigimo laikas retai atitinka pradinius užsibrėžtus planus. Taip yra dėl nenumatytų atvejų, kurie daro įtaką galutiniam projekto baigimo laikui. Šiame straipsnyje autoriai pristato metodą, kuris pagerina statybos grafikų patikimuma. Jis grindžiamas laiko rezervo paskirstymo idėja, padedančia sumažinti neigiamus atsitiktinių trikdžių poveikius vykdant projektą. Autoriai pritaiko veiksmingą būdą, kuris leidžia išvengti daugelio sutrikimų vykdant projektą. Siūlomas metodas pagrįstas modeliavimu ir matematiniu programavimu, darbe pateiktas jo taikymo pavyzdys. Gauti rezultatai, taikant siūlomą metoda, buvo lyginami įvairiais požiūriais. Metodas leidžia sumažinti išlaidas, kai atsitiktinėmis sąlygomis nukrypstama nuo planuojamų terminų.Reikšminiai žodžiai: statybos vykdymo grafikas, tvarus sprendimas, patikimas grafikas, rezervas, rizikos valdymas, projektų valdymas, tiesinis programavimas.